Penerapan Lean Manajemen Pada Pelayanan Rawat Jalan Pasien BPJS Rumah Sakit - Sarah Rania Annisa; Syalisa Syabil; Huwaydi Azzam Yusuf; Acim Heri Iswanto (Jurnal Rumpun Ilmu Kesehatan, 2023)
Outpatient services are an important part of health services provided by hospitals. However, some BPJS hospitals experience obstacles in providing efficient and quality outpatient services, such as long queues, long waiting times, and lack of a good management system. the application of Lean Management to the outpatient services of BPJS patients in hospitals can help hospitals improve operational performance, so as to increase public trust in BPJS Health. This study aims to analyze the application of Lean Management to the outpatient services of BPJS patients in hospitals. This research uses a literature study method or Systematic Literature Review using the Google Scholar search engine and journal databases, such as Researchgate. The results showed that most outpatient service activities for BPJS patients still have patient waiting times below the established service standards. In analyzing the flow that patients go through, each activity is identified into two groups, namely Value Added (VA) as an activity that is considered necessary and profitable and Non Value Added (NVA) as an activity that is considered unnecessary. Based on the percentage of waste in the form of the largest waiting time can be described, namely, 35.1% in the registration process, 30.2% in the poly examination process, and 20.7% in the process of receiving drugs in the pharmaceutical installation